2021
DOI: 10.1007/s10750-021-04651-5
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and vegetation carbon stock in mangrove forests of the Andaman Islands, India

Abstract: The present study estimated plant biomass in mangrove forests of the Andaman Islands, India. The mean above-ground biomass was 469.20 ± 41.25 Mega-gram/ha (Mg ha -1 ), while the mean belowground biomass was 166.78 ± 12.79 Mg ha -1 . The total mean biomass of Andaman mangrove forest was 635.98 ± 12.79 Mg ha -1 and its corresponding vegetation carbon stock was 290.26 ± 24.75 Mg C ha -1. Among the 6 forest divisions, Little Andaman recorded the highest mean biomass per unit area (1,081.26 ± 424.67 Mg ha -1 ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…On the other hand, the aboveground carbon content was double that reported in Nayarit, Mexico, for fringe and riverine mangroves (36.22 Mg C ha −1 ) [15] and 48 to 77% higher than that reported in Baja California Sur, Mexico, dwarf mangroves of R. mangle, L. racemosa, and A. germinans (13.6-31.6 Mg C ha −1 ) [78]. The lower carbon contents at these sites could be because they were inhabited by species with small DBHs and low densities, agreeing with Ragavan et al [68], who mentioned that larger diameter trees contain more carbon reserves due to the positive correlation between the density of trees with biomass and carbon, while Velázquez-Pérez et al [10] concluded that a higher number of juvenile trees is associated with lower carbon content. Carbon storage also varies with climatic conditions, hydrogeomorphic configurations, and mangrove species [79].…”
Section: Aboveground Carbonsupporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand, the aboveground carbon content was double that reported in Nayarit, Mexico, for fringe and riverine mangroves (36.22 Mg C ha −1 ) [15] and 48 to 77% higher than that reported in Baja California Sur, Mexico, dwarf mangroves of R. mangle, L. racemosa, and A. germinans (13.6-31.6 Mg C ha −1 ) [78]. The lower carbon contents at these sites could be because they were inhabited by species with small DBHs and low densities, agreeing with Ragavan et al [68], who mentioned that larger diameter trees contain more carbon reserves due to the positive correlation between the density of trees with biomass and carbon, while Velázquez-Pérez et al [10] concluded that a higher number of juvenile trees is associated with lower carbon content. Carbon storage also varies with climatic conditions, hydrogeomorphic configurations, and mangrove species [79].…”
Section: Aboveground Carbonsupporting
confidence: 86%
“…The biomass generated in the mangroves of Úrsulo Galván (120.5 Mg ha −1 at a density of 3515 ind ha −1 ) was lower than that reported in the Gulf of Montijo, Panama (176 Mg ha −1 at a density of 8267 ind ha −1 ) [67], the Andaman Islands, India (469.20 Mg ha −1 at a density of 1767 ind ha −1 ) [68], in Bangladesh (157 Mg ha −1 at a density of 255 ind ha −1 ) [69], and in the Amazon region, Brazil (145 Mg ha −1 ) [70]. The results are close to those recorded in the La Encrucijada Biosphere Reserve, Chiapas, of 131.8 Mg ha −1 [14] and Peninsular Malaysia of 108.27-155.58 Mg ha −1 [19] and higher than those found in Kelantan, Malaysia, of 2.66 Mg ha −1 at a density of 1170 ind ha −1 [71].…”
Section: Aboveground Biomassmentioning
confidence: 68%
“…Mangrove forests have the largest organic carbon (C ORG ) stocks of any of earth's ecosystems, with a global mean total forest stock of 692.8 ± 23.1 (±1 SE) Mg C ORG ha −1 (updated from [8] with [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]). Soil standing stocks average 516.4 ± 19.8 Mg C ORG ha −1 over the upper 1 m depth, accounting for 74% of total ecosystem standing stocks.…”
Section: Carbon Stocksmentioning
confidence: 99%
“…These large amounts of C ORG reflect rapid rates of soil accumulation on the forest floor, sustained accumulation over long time periods, and high rates of primary productivity. In contrast, global mean aboveground and belowground mangrove biomass average 105.8 ± 4.2 Mg C ORG ha −1 (±1 SE) and 68 Mg C ORG ha −1 , respectively, as updated from Alongi [8] with new data [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], which underscores the dominance of the soil component.…”
Section: Carbon Stocksmentioning
confidence: 99%
See 1 more Smart Citation